If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-17a+4(a-7)=-3(3a-1)+1
We simplify the equation to the form, which is simple to understand
-17a+4(a-7)=-3(3a-1)+1
Reorder the terms in parentheses
-17a+(+4a-28)=-3*(3a-1)+1
Remove unnecessary parentheses
-17a+4a-28=-3+*(+3a-1+)+1
Reorder the terms in parentheses
-17a+4a-28=+(-9a+3)+1
Remove unnecessary parentheses
-17a+4a-28=-9a+3+1
We move all terms containing a to the left and all other terms to the right.
-17a+4a+9a=+3+1+28
We simplify left and right side of the equation.
-4a=+32
We divide both sides of the equation by -4 to get a.
a=-8
| 15ab+13a-15ab= | | 2m-5m=6 | | 45x+5=50graph | | 3(2x-3)+9=6x | | x+7=-3(5-x) | | 1y=-4 | | (-3)-2.2-9-(-12)= | | 8x-5=2(4x-3) | | 2.2x=-22 | | 3x+12=-3x+20 | | 2(3x+1)+4=2-x | | 18x+2(x+7)=-6 | | 37+12+=85 | | 7x+9=4x+3 | | 0.3x+1.1=3.5 | | 2*(3-x)+7=4x-5*(2+x) | | 0.3+1.1=3.5 | | 2(3-x)+7=4x-5(2+x) | | 5x=3x+20 | | 32-3x=2x-28 | | (22b-9)-7(3b+4)=-4 | | 3x-4(x-2)(X^2+6x^2-1)-7= | | 4x+2-3x=18 | | 5a(a+3)=2a(2a-5) | | 2(3+2w)+1=-5 | | x(x-4)+56=x*x | | 8x+2=3x-2 | | -9x+11=2x+11 | | 7e+10=4e+28 | | 6x^3-6x+1=0 | | -7x+1=-13 | | Y=3.5 |